Reconciliation barometers: tools for postconflict policy design - Cole, Elizabeth A. (International journal of transitional justice, 2019)
This article provides a comprehensive overview of several efforts at creating reconciliation barometers in 10 countries worldwide. The discussion is based on reflections from the originators of the barometers themselves convened in a workshop in 2016 about methodology, definitions, challenges and outcomes of these efforts to longitudinally measure reconciliation in postconflict contexts. We conduct a cross-barometer comparison and conclude that the different barometers have many more similarities than differences - a surprising finding considering the variety of contexts they represent. With the proliferation of efforts to develop reconciliation barometers in the past decade, we propose a new research agenda to contribute to a growing need to better understand the consumption of these tools by policy makers and implementers, as well as how they are best developed and disseminated.